Cutaneous Hemangioma With Epithelioid Features Harboring TPM3/4::ALK Fusions : A Distinct Entity or a Molecular Variant of Epithelioid Hemangioma? - Dehner, Carina A; Jour, George; Gassenmaier, Maximilian; Michal, Michael; de Saint Aubain, Nicolas; Papke, David J; Umphress, Brandon; Li, Aofei; Tanner, Mark M; Calonje, Eduardo; Brenn, Thomas; Fletcher, Christopher D M; et al. (The American journal of surgical pathology, 2025)
Vascular neoplasms with epithelioid cytomorphology encompass a wide spectrum of benign and malignant lesions, including epithelioid hemangioma (EH), cutaneous epithelioid angiomatous nodule (CEAN), epithelioid hemangioendothelioma (EHE), and epithelioid angiosarcoma (EAS). Recently, the first case of a cutaneous hemangioma with epithelioid features harboring a TPM3::ALK fusion was reported. Herein, we report 4 additional cases, including 1 case with an alternate TPM4::ALK fusion, and expand on the clinicopathologic and molecular genetic features of these unusual vascular lesions. Including the previously reported case, 5 tumors occurred in 4 male and 1 female patients with a median age of 14 years (range: 2 to 38 y) and involved the shoulder region (2), the lower extremity (1), trunk (1), and head and neck (1). Clinical follow-up (3 patients; 60%) showed no evidence of disease at the last follow-up (median: 5 mo; range: 1 to 16 mo). Histologically, all tumors showed highly similar morphologic features, including an epidermal collarette, well-formed vascular channels composed of epithelioid endothelial cells with intracytoplasmic vacuoles, and admixed inflammatory cells. Immunohistochemically, all tumors were positive for vascular markers such as ERG and CD31, along with strong and diffuse cytoplasmic expression of ALK. RNA sequencing revealed recurrent TPM3 exon 8 :: ALK exon 20 (4) and TPM4 exon 7 :: ALK exon 20 fusions (1). We conclude that cutaneous hemangiomas with epithelioid features harboring TPM3/4::ALK fusions show consistent morphologic, immunophenotypic, and molecular genetic features. It remains to be determined whether this neoplasm represents a distinct entity or a molecular variant of epithelioid hemangioma.
Keywords: Young Adult; TPM4; Hemangioma; epithelioid hemangioma; Gene Fusion; fenotyp; Male; Epithelioid Cells; Phenotype; hemangiom; Child, Preschool; Anaplastic Lymphoma Kinase; mladý dospělý; tropomyosin; Adolescent; epiteloidní buňky; Skin Neoplasms; Child; fúze genů; dítě; Adult; cutaneous hemangioma; dospělí; mužské pohlaví; anaplastická lymfomová kináza; mladiství; ALK﻿; předškolní dítě; lidé; ženské pohlaví; Humans; nádory kůže; TPM3; Female; Tropomyosin; Biomarkers, Tumor; nádorové biomarkery